Population dynamics and growth of Galinsoga ciliata in relation to method of cultivation, crop type and altitude - MISRA, J; PANDEY, H N; TRIPATHI, R S (The Indian Journal of Agricultural Sciences, 2013)
Population dynamics and growth (dry-matter yield) of Galinsoga ciliata (Rafin.) Blake a serious weed in hillagroecosystem of Meghalaya was studied for two years in radish (Raphanus sativus L.) and maize (Zea mays L.) fieldsunder slash and burn agriculture (jhum) and terrace cultivation situated at high and low altitudes of Meghalaya, north-eastIndia. Two to three seedling cohorts were recruited in the crop fields at the low altitude, while at high altitudeseedlings were recruited 'invariably in three successive cohorts. Seedling emergence in the first cohort was significantlyhigher than in the second and/or third cohort. Associated crop, method of cultivation and altitudinal variation significantlyinfluenced seedling recruitment and survivorship and half lives of cohorts of G. ciliata.